STUDI DEVIASI PENERAPAN ASPEK HUKUM PENGADAAN KONSTRUKSI - Erdin Fahlefi; Akhmad Suraji; Albani Musyafa (CV. ALIM'SPUBLISHING, 2023)
In construction procurement in Indonesia there are still deviations in the tender process. The deviation is caused by an opportunity during the construction bidding process. The service providers are mutually looking for opportunities to seek personal or group benefits or from the working group that makes these deviations. This causes state losses due to deviations in the construction bidding process. This research was conducted by collecting data from institutions that have the authority to decide whether or not deviations occur in the auction process. The institution authorized to decide whether or not a deviation occurs is the Commission for the Supervision of Business Competition of the Republic of Indonesia (KPPU RI). This study uses a questionnaire to find out how much the causes and impacts on state losses are caused by deviations in the auction process and uses the Probability and Impact Matrix method to determine the level of implication values of the causes and impacts of deviations in each case using a case base analysis approach. The results obtained based on the decision are as many as 12 types of deviation based on the case decision. The impact of deviations that occur in construction procurement is material and immaterial losses. The causes of deviation in construction procurement are caused by four factors, namely the factor of wanting to obtain personal or group benefits, opportunities, pressure and business climate. The most contributing factor to the occurrence of deviation is the combined conspiracy and vertical conspiracy resulting in a value of 11.38%.